Teachers' democratic assignment: a critical discourse analysis of teacher education policies in Ireland and Sweden. Issue 6 (2nd November 2019) - Mooney Simmie, Geraldine; Edling, Silvia
ABSTRACT: The needs of a globalized economy are rapidly changing what is legitimated as school knowledge and values, and calling up new understandings of teachers' role in stimulating democratic spaces. We have termed this Teachers' Democratic Assignment . We examine changing notions of teachers' democratic assignment in Ireland and Sweden using a Critical Discourse Analysis. We tested our hypothesis that teachers' democratic assignment has changed in unprecedented ways using an analysis of policy documents in teacher education. Our findings reported a substantive converging paradigm shift from a predominantly progressive (reconstructivist) curriculum discourse where democracy was seen as inextricably linked to everyday practice in the early years of this century, to a more essentialist (perennialist) discourse in recent times. The findings will have interest for a wider audience and have implications for the role of democracy in teacher education as well as the question of education as a social responsibility for a vibrant democracy.